CBD-conjugated BMP-inhibiting exosomes on collagen scaffold dual-target Achilles tendon repair: Synergistic regeneration and heterotopic ossification prevention - Yan Xu; Jiaqiang Huang; Yingjie Mai; Zhiyuan Zhang; Siqi Li; Haofeng Lin; Fuxin Wei; Yang Chen (Materials Today Bio)
Tendon injuries in the aging population are often complicated by heterotopic ossification (HO), hindering functional recovery. Exosomes from tendon stem/progenitor cells (TSPCs) promote regeneration but may also induce osteogenesis, contributing to HO. Preconditioning with the BMP inhibitor LDN193189 and modification with collagen-binding peptides (CBD) can enhance the tenogenic potential of exosomes while mitigating osteogenic effects. We evaluated the efficacy of a 3D-printed scaffold loaded with LDN-preconditioned, CBD-modified exosomes (3D-CBD@LDN/Exos) derived from CD26+ TSPCs in promoting Achilles tendon repair and preventing HO in aged Sprague-Dawley rats. CD26+ TSPCs were isolated from rat tendons, and exosomes were collected after LDN treatment and subsequently modified with CBD. A scaffold composed of PLGA and collagen I was fabricated via 3D printing and loaded with the exosomes. Rats (20 months old) with 6-mm Achilles tendon defects were randomly assigned to Control, 3D-Exos, 3D-LDN/Exos, or 3D-CBD@LDN/Exos groups, and tendon regeneration was evaluated at 4 and 12 weeks using histology, ECM quantification, micro-CT, and biomechanical testing. At 12 weeks, the 3D-CBD@LDN/Exos group exhibited near-normal histology, enhanced collagen and sGAG deposition, biomechanical properties comparable to native tendons, and significantly reduced HO, indicating that this dual-targeted strategy holds promise for tendon repair.